Reduksi Harmonisa Pada Saluran Distribusi Tenaga Listrik Dengan Filter Daya Aktif - ., Fitriadi; Hamid, M. Imran; Herisanjani, Herisanjani; Firmansyah, Firmansyah; Hendri, Zulka (Elektron : Jurnal Ilmiah, 2023)
The large use of power converters in distribution lines causes poor power quality such as high produces harmonics in an electric power system that arises due to the operation of non-linear electrical equipment. The presence of harmonics in the power system distribution results in a very large loss in the system. In this paper had been done a simulation of power quality improvement through harmonic reduction using parallel active power filter. Active power filters work with control techniques based on the concept of instantaneous power to determine the amount of compensation currents that must be generated by the power compensator power circuit. The compensating current references generated by the control circuit are used by the hysteresis type controller to provide harmonic compensation arising. From the result of simulation using Simulink MATLAB, the harmonic value (THD) decrease caused by the 3 phase rectifier load on a distribution network which is used as case example. The harmonic value before compensated on the network is 27.85% at each phase, while after computing the harmonic value of the network decreases to 1,43% in R phase, 1,49% in S phase, and 1,34% in T phase.